Differentiating lower motor neuron syndromes. Issue 6 (21st December 2016) - Garg, Nidhi; Park, Susanna B; Vucic, Steve; Yiannikas, Con; Spies, Judy; Howells, James; Huynh, William; Matamala, José M; Krishnan, Arun V; Pollard, John D; Cornblath, David R; Reilly, Mary M; et al.
Abstract : Lower motor neuron (LMN) syndromes typically present with muscle wasting and weakness and may arise from pathology affecting the distal motor nerve up to the level of the anterior horn cell. A variety of hereditary causes are recognised, including spinal muscular atrophy, distal hereditary motor neuropathy and LMN variants of familial motor neuron disease. Recent genetic advances have resulted in the identification of a variety of disease-causing mutations. Immune-mediated disorders, including multifocal motor neuropathy and variants of chronic inflammatory demyelinating polyneuropathy, account for a proportion of LMN presentations and are important to recognise, as effective treatments are available. The present review will outline the spectrum of LMN syndromes that may develop in adulthood and provide a framework for the clinician assessing a patient presenting with predominantly LMN features.